Pengaruh Pengelolaan Dana Desa Terhadap Peningkatan Kesejahteraan Masyarakat Desa Meken Detung Kecamatan Kangae Kabupaten Sikka - Kristina Dua Goan; Antonius Philipus Kurniawan; Elisabet Luju (Jurnal CUAN Universitas Nusa Nipa Maumere, 2023)
The background of this research is the low level of welfare of the people of Meken Detung Village, Kangae District, Sikka Regency, even though it has been supported by financial assistance in the form of village funds. The purpose of this study was to find out 1) the description of village fund management and community welfare and, 2) the influence of village fund management in improving the welfare of the people of Meken Detung Village, Kangae District, Sikka Regency. The research method uses an associative quantitative descriptive method. The population in this study was the village community of Meken Detung with a total sample of 84 people. Data were collected through questionnaires and descriptive analysis and inferential statistics, namely simple linear regression. Hypothesis testing was carried out through a t test with the help of the SPSS 25 software program. The results of this study indicate that the effect of village fund management in Meken Detung, Kangae District, Sikka Regency, that the independent variable has a positive and significant effect on improving people's welfare in Meken Detung Village, Kangae District, Sikka Regency.